Associations between type III interferons, obesity and clinical severity of COVID-19 - Alalwan, Dana; Leon, Alejandro Abner Garcia; Saini, Gurvin; Gaillard, Colette; Negi, Riya; Heckmann, Camille; Kenny, Grace; Feeney, Eoin; Cotter, Aoife G.; Kelly, Christine; Carr, Michael; de Barra, Eoghan; et al. (Frontiers in Immunology, 2025)
IntroductionSevere COVID-19 is characterized by hyperimmune host responses contributing to airway damage and acute respiratory distress syndrome. Type III interferons (IFN), including IFN lambda 4 (IFNλ4), expressed in individuals harboring the rs368234815-ΔG allele, are implicated in host immune responses to viral infections, including SARS-CoV-2.MethodsWe investigated associations between IFNλ4 expression through genotyping and COVID-19 disease severity in 853 laboratory-confirmed SARS-CoV-2 cases enrolled in the All-Ireland Infectious Diseases Cohort. Additionally, we measured plasma levels of Type I, II and III IFN using quantitative immunoassays along with IFNλ4 expression and COVID-19 disease severity in a sub-group [n=321 (37.6%)] with samples available within 10 days of symptom onset. IFNλ4 was expressed in 382 (44.8%) but expression was not significantly associated with COVID-19 disease severity.ResultsWithin the sub-group, we found no consistent associations between IFNλ4 expression and circulating IFNs. However, we observed significantly increased expression of IFNλ1 and IFNλ2 in severe COVID-19 (P<0.01), with IFNλ2 remaining significantly associated after adjustment for age, sex, ethnicity, and comorbidities, including obesity (BMI≥30 kg/m2) (P<0.001). Interestingly, although IFNλ2 levels were significantly higher in subjects with obesity, the association between higher IFNλ2 and COVID-19 disease severity was only observed in individuals without obesity (P<0.01).ConclusionThese data reveal an important role for IFNλ2 as an immune correlate that predicts COVID-19 disease severity, which may be masked in those with obesity.